Drip and ship versus direct to endovascular thrombectomy: The impact of treatment times on transport decision-making. (June 2018) - Holodinsky, Jessalyn K; Patel, Alka B; Thornton, John; Kamal, Noreen; Jewett, Lauren R; Kelly, Peter J; Murphy, Sean; Collins, Ronan; Walsh, Thomas; Cronin, Simon; Power, Sarah; Brennan, Paul; et al.
Introduction: In ischaemic stroke care, fast reperfusion is essential for disability free survival. It is unknown if bypassing thrombolysis centres in favour of endovascular thrombectomy (mothership) outweighs transport to the nearest thrombolysis centre for alteplase and then transfer for endovascular thrombectomy (drip-and-ship). We use conditional probability modelling to determine the impact of treatment times on transport decision-making for acute ischaemic stroke. Materials and methods: Probability of good outcome was modelled using a previously published framework, data from the Irish National Stroke Register, and an endovascular thrombectomy registry at a tertiary referral centre in Ireland. Ireland was divided into 139 regions, transport times between each region and hospital were estimated using Google's Distance Matrix Application Program Interface. Results were mapped using ArcGIS 10.3. Results: Using current treatment times, drip-and-ship rarely predicts best outcomes. However, if door to needle times are reduced to 30 min, drip-and-ship becomes more favourable; even more so if turnaround time (time from thrombolysis to departure for the endovascular thrombectomy centre) is also reduced. Reducing door to groin puncture times predicts better outcomes with the mothership model. Discussion: This is the first case study modelling pre-hospital transport for ischaemic stroke utilising real treatment times in a defined geographic area. A moderate improvement in treatment times results in significant predicted changes to the optimisation of a national acute stroke patient transport strategy. Conclusions: Modelling patient transport for system-level planning is sensitive to treatment times at both thrombolysis and thrombectomy centres and has important implications for the future planning of thrombectomy services.